FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN KABUPATEN/KOTA DI PROVINSI BALI - Putra, I Made Yogi Maha; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 10 (2020): VOL 9 NO 10, OKTOBER 2020 (2152 - 2389), 2020)
Disparity between regions shows that there are differences in the level of development and the level of welfare between regions, making this problem serious. The purpose this research (1) analyze direct effect education level, working population, and investment on economic growth regencies / cities in Bali; (2) analyze direct effect education level, working population, investment and economic growth on poverty levels districts / cities in Bali; (3) analyze the indirect effects of education level, working population, and investment on poverty levels through economic growth in districts / cities in Bali. Analysis used path analysis. The results of this study (1) Education level and working population have significant positive effect, investment doesn’t have effect on economic growth of districts / cities in Bali; (2) Education level, working population, investment, and economic growth have a significant negative effect on the poverty level of districts / cities in Bali; (3) Economic growth partially mediates the effect of the level of education and the number of working people on the poverty level of districts / cities in Bali. However, economic growth isn’t able mediate effect investment on poverty level districts / cities in Bali.   Keywords: education level, working population, investment, economic growth, poverty level